Ras proteins control mitochondrial biogenesis and function in Saccharomyces cerevisiae - Hlavatá, L; Nyström, T (Folia microbiologica, 2003)
The evolutionarily conserved Ras proteins function as a point of convergence for different signaling pathways in eukaryotes and have been implicated in both aging and cancer development. In Saccharomyces cerevisiae the plasma membrane proteins Ras1 and Ras2 are sensing the nutritional status of the environments, e.g., the abundance and quality of available carbon sources. The cAMP-protein kinase A pathway is the most explored signaling pathway controlled by Ras proteins; it affects a large number of genes, some of which are important to defend the cell against oxidative stress. In addition, recent analysis has shown that the Ras system of yeast is involved in the development of mitochondria and in regulating their activity. As a sensor of environmental status and an effector of mitochondrial activity, Ras serves as a Rosetta stone of cellular energy transduction. This review summarizes the physical and functional involvement of Ras proteins and Ras-dependent signaling pathways in mitochondrial function in S. cerevisiae. Since mitochondria produce harmful reactive oxygen species as an inevitable byproduct and are partly under control of Ras, illuminating these regulatory interactions may improve our understanding of both cancer and aging.
Keywords: Mitochondria; Saccharomyces cerevisiae; signální transdukce; Ras proteiny; Signal Transduction; ras Proteins; mitochondrie